Borderline personality disorder Athens study: a quasi-experimental pragmatic trial for the assessment of a public, psychodynamic, stepped care service for borderline personality disorder patients - Malogiannis, Ioannis; Anagnostaki, Lida; Aspradaki, Maria; Aristotelidis, Panagiotis; Karambela, Katerina; Amperiadou, Maria; Efthymiou, Vasiliki; Kriezi, Phaithra; Theodoridou, Ioanna; Stefanatou, Pentagiotissa; Konstantakopoulos, George; Souliotis, Kyriakos; et al. (Frontiers in Psychiatry, 2025)
BackgroundBorderline personality disorder (BPD) is a common mental disorder that severely impairs patients’ psychosocial functioning and quality of life and results in prolonged use of health services. Although psychotherapy is recommended as the most effective treatment for patients with BPD, their complex emotional needs can be met in everyday clinical practice by developing integrative, holistic, personalized mental health services tailored to their needs.Aim and hypothesisThe aim of our study was to evaluate the effectiveness of a specialized psychodynamic stepped-care service for BPD patients. Our hypothesis is that patients receiving this specialized health-care service will show greater improvement in clinical, functional and quality of life than patients receiving a treatment as usual (TAU) service. In addition, specialized health-care services will prove to be more cost effective.Method and designA quasi-experimental clinical trial will be conducted. The study is designed to include 212 BPD patients who will be non-randomly assigned to specialized health care services and to two TAU centers. Patients will be recruited at each site following the routine clinical pathways of referral at each center. The primary outcome measures are BPD severity, suicide attempts and hospital admissions. The secondary outcome measures will include measures of general psychopathology, psychosocial functioning, quality of life and retention in treatment. In addition. An economic evaluation from a societal perspective will be conducted.DiscussionThe development of complex individualized stepped-whole care public interventions for BPD patients requires extended research in everyday clinical practice conditions. In this study, we describe the design and implementation of a pragmatic trial to evaluate this type of health service for BPD patients, and we discuss the strengths as well as the problems and how these can be mitigated.Trial registrationClinical Trials gov.: ClinicalTrials.gov ID: NCT06392139 (Protocol ID No. 404/06-07-202).